Market and corporate governance in the new international environment Indonesian experiences - Joedo, Prasetijono Widjojo Malang (2000)
The economic crises in Indonesia were only rooted in financial sector fragilities. It was also related to poor managerial performance in both public and private institution. The implementation of public and corporate governance indicates several weaknesses. First, the Indonesia economy, shocked by market sentiment combined with inefficiency in the micro policy implementation, has caused the lack of coordination in conducting macroeconomics policies. Second, the culture of corruption, collusion and nepotism found in most level in public and private institutions across regions and sectors has proliferated. This has accelerated the deterioration process of the political and economic situation, which was also worsened by the lack of discipline and poor implementation of law and order. Specifically, poor implementation of public and corporate governance has caused economic problems even more difficult to solve. Finally, lack of transparency in almost every aspect of administrative and decision-making process creates uncertainty and raises the country risk. This paper discusses the progress of efforts in establishing good corporate governance in Indonesia in the context on an international environment. Globalization and decentralization ideologies give challenge and opportunities for Indonesia for implementing good corporate governance. However, social and political pressures still play a more important role in determining the directions of successful corporate governance. In order to reach the optimum economic and social solutions to this dilemma, diversities across the regions and culture should be taken into account. The government is expected to play an important role as facilitator in establishing good corporate governance by considering technical and economic efficiency grounds. The government, in the cooperation with the legislature includes law and regulatory infrastructure to resolve agency or moral hazard problems. Control in the macro and micro levels is also important to establish and facilitate efficient mechanisms at various levels of management. However, this condition requires a clear and applicable law and regulatory framework depicting horizontal and vertical power sharing. This requirement is very important to determine the revenue sharing across regions and levels of government.
Includes bibliographical references (page 100).
Keywords: Corporate governance -- Indonesia